Blockchain in Healthcare Today 2022 Predictions - Conway, Daniel; Venkataraman, Mohan; Laverick, Daniel; Pelin, Gabriela; Hasselgren, Anton (Blockchain in Healthcare Today, 2022)
Each year Blockchain and Healthcare Today reaches out to journal board members, annual ConV2X Symposium speakers and ecosystem subject matter experts to share their near term views and perspectives for blockchain technology advances in healthcare. Representing perspectives from Asia, Europe and North America, the article presents insights into where authors anticipate market opportunities and gaps that should be addressed for regional and global collaboration, governance and efficiency for the year 2022.